The Economics of Justice as Fairness - Antonio Abatemarco; Francesca Stroffolini (ECINEQ - Society for the Study of Economic Inequality; ZBW – Leibniz Information Centre for Economics, 2017)
In this paper we challenge the common interpretation of Rawls' Theory of Justice as Fairness by showing that this Theory, as outlined in the Restatement (Rawls 2001), goes well beyond the definition of a distributive value judgment, in such a way as to embrace efficiency issues as well. A simple model is discussed to support our interpretation of the Difference Principle, by which inequalities are shown to be permitted as far as they stimulate a greater effort in education in the population, and so economic growth. To our knowledge, this is the only possibility for the inequality to be `bought' by both the most-, and above all, the least-advantaged individual as suggested by the Difference Principle. Finally, by recalling the old tradition of universal ex-post efficiency (Hammond 1981), we show that a unique optimal social contract does not exist behind the veil of ignorance; more precisely, the sole set of potentially optimal social contracts can be identified a priori, and partial justice orderings derived accordingly.
Keywords: D63; D31; J31; 330; justice; Rawls; inequality; social contract